The employment of fitting programs for deuteron polarization calculation in a nuclear polarized target - Belyaev, A.A.; Dzyubak, A.P.; Luchanin, A.A. (Вопросы атомной науки и техники, 2000)
We have developed the fitting program used for deuteron polarization calculation. The simulation has been done for the deuterated 1,2-propanediol-D8 as a target material. Analyses of the uncertainties sources have been performed. The polarization calculated was P=+34.0% and P = -36.6% for above-mentioned target material.